The School Experience of Arab LGBT Students in Israel - Said, Anton (Wydawnictwo Naukowe UAM, 2017)
The purpose of the research is to study the school experience of Arab Lesbians, Gays, Bisexuals and Transgender (LGBT) in the state of Israel from own point of view. The research question is: what is the school experience of Arab LGBT graduates of the Israeli educational system in high schools where the language of learning is Arabic? This is a quantitative research, based on a questionnaire completed by 51 Arab LGBT, graduates of the Israeli educational system. They attended high schools where the language of learning is Arabic; 69.8% (N=37) of them were completed by males, 28.3% (N=15) by females, and 1% (N=1) by transgender. 62.3% reported that their sexual inclination is homosexual, 22.6% lesbian, 13.2% bisexual, and transgender one (1%). The ages of the respondents range from 18 to 32. The research participants were recruited through the ‘snowball sample’ method. The initial request was made to my personal Facebook friends whom I knew were LGBT, and they disseminated the questionnaire to additional LGBT friends they knew. The questionnaire examined the school experience in general and their perception of the role of the Arab educational counselor particularly on the topic of the sexual orientation and sexual identity, attitudes towards LGBT students, and degree of the influence of traditional Arab society on his role as a school counselor whose role is to advise, help, and accompany all the students so as to integrate in the school and in society in the best possible way. 51 questionnaires were examined in three independent variables of respondents on which the research focuses: the sector to which the respondent’s school belongs, the respondent’s religion, and the school location.
Doświadczenie szkolne uczniów arabskich z grupy LGBT w Izraelu
Keywords: sociology; LGBT studies; LGBT in Arab culture; school counselor; Arab Sector in Israel